2020
DOI: 10.3390/en13143614
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microwave Thermal Stress Fracture Characteristics and Size Effect of Sandstone under Microwave Heating

Abstract: Microwave-induced rock fracture is one of the promising approaches of achieving non-blasting continuous mining and assisted mechanical rock breaking. It is of great theoretical and practical significance to study the temperature effect and fracture characteristics of rocks of different sizes under microwave heating; however, there are few studies in this field. Microwave heating of φ 50 × 100 mm, φ 50 × 50 mm, and φ 50 × 25 mm sandstone samples with different heating powers and times was performed to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The energy absorbed by rock through the exposure to microwave radiation is converted to heat. The amount of heat produced by microwaves in a particular rock depends in general on water content, size (Gao et al 2011), mineral composition (Nicco et al 2020), andschistosity (He et al 2019) of the rock. Moreover, microwave radiation conditions such as power level, exposure time and distance from rock have an influence on temperature intensity and distribution (Wang and Forssberg 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The energy absorbed by rock through the exposure to microwave radiation is converted to heat. The amount of heat produced by microwaves in a particular rock depends in general on water content, size (Gao et al 2011), mineral composition (Nicco et al 2020), andschistosity (He et al 2019) of the rock. Moreover, microwave radiation conditions such as power level, exposure time and distance from rock have an influence on temperature intensity and distribution (Wang and Forssberg 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Rock specimens of various sizes underwent microwave heating tests by Gao Feng et al. (Gao et al., 2020) And the results showed that these rocks have different temperature responses and crack expansion patterns. Thermocouples were implanted into the granite specimens to further investigate the variation in interior temperature.…”
Section: Introductionmentioning
confidence: 99%
“…ere is always a strong demand for e cient and rapid drilling in hard rock strata. Based on this, numerous scholars begin to search for new methods of rock crushing [1]. It is widely recognized that cyclic impact loading can cause fatigue failure inside the rock [2][3][4].…”
Section: Introductionmentioning
confidence: 99%